Public Work Engineering Leadership Challenges in Covid-19 Era: A Boss, A Manager, or A Leader - Dr. Thewodros K. Geberemariam (International Journal of Engineering and Management Research, 2020)
Although remote working is not new, it has never been deployed on such a massive scale in a short period as it has been in the current situation. Owing to Covid-19, organizations that never relied on a remote workforce have been forced to operate in a virtual environment. Hence, many public work directors and leaders currently find themselves utilizing unusual channels to engage deeply with stakeholders and employees virtually. This makes the task of leading, operating, planning, organizing, directing, and coordinating various activities of the Public Works Department more complicated. Every day, demonstration of great leadership is required in an almost exclusively virtual workplace to recognize and reward great performance and address performance challenges by making difficult, authentic, and empathetic decisions. Leaders are also required to be context-sensing communicators having a “perfect pitch” when communicating with a different audience in various situations. This article focuses on leaders’ transition from leading in the office to leading in a remote environment in the Covid-19 era and discuss leader–team dynamics through the lens of “transitioning from a boss or a manager to a leader” by making aggressive efforts to view the landscape through the eyes of the people they lead, coach, support, and inspire.